Analisis Semiotika Konsep Bullying Dalam Drama Korea Pyramid Game - Fitri, Ghina Fadhilah; Aslinda, Cutra (CV. ITTC INDONESIA, 2025)
This study discusses the findings of the bullying concept contained in the Korean drama Pyramid Game using Charles Sanders Peirce's semiotics with a triangle of meaning, namely sign, object, and interpretant. This study aims to focus on the bullying concepts contained in the Korean drama Pyramid Game, namely the concept of physical bullying, the concept of verbal bullying, the concept of relational bullying and the concept of cyberbullying. And a critical assessment of the main character's response to bullying will explore how feelings of isolation, anxiety, and efforts to fight back can change social perceptions of victims and perpetrators. These findings lead to a deeper understanding of the bullying concepts contained in Korean dramas, which also show bullying in South Korean teenagers. The method used in this study is qualitative research with Charles Sanders Peirce's semiotic analysis. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions or verification. The results of this study are that there are 3 episodes containing the concept of physical bullying, 4 episodes containing the concept of verbal bullying, 3 episodes containing the concept of relational bullying and 2 episodes containing the concept of cyberbullying.